Mechanistic studies of rhodium-catalysed intermolecular hydroacylation - Barwick-Silk, J (2018)
Chapter 1 – Introduction: The concept of rhodium-catalysed intermolecular hydroacylation is introduced. The research that has led to significant improvements in substrate scope and catalytic activity are described, with the reactions being classified into three sub-groups: aldehyde-tethered hydroacylation, alkene-tethered hydroacylation and non-tethered hydroacylation. The mechanistic studies that have facilitated these developments are then detailed. Chapter 2 – Mechanistic Studies of β-Amido Aldehyde Hydroacylation: One of the recent developments in aldehyde-tethered hydroacylation has been the use of β-amido aldehyde substrates. This chapter describes the mechanistic studies of the reaction of a β-amido aldehyde substrate with 1-octyne, catalysed by the Rh(I)-complex [Rh(cis-κ2-P,P-DPEPhos)(acetone)2][BArF4]. Chapter 3 – Cyclotrimerisation and Optimisation of Hydroacylation: In chapter 2, cyclotrimerisation of 1-ocytne was discovered to be a competitive side-reaction with hydroacylation under certain conditions. The mechanism of the cyclotrimerisation reaction is explored with the pre-catalyst [Rh(cis-κ2-P,P-DPEPhos)(acetone)2][BArF4], and the point at which the reactions become competitive is discovered. This understanding is then used to optimize the catalyst loading, reagent stoichiometry, reaction concentration and reaction temperature, leading to the realisation of an exceptionally efficient, and selective, gram-scale hydroacylation process. Chapter 4 – Non-tethered Aldehyde Hydroacylation of Acrylates: The discovery of a non-tethered aldehyde Tishchenko reaction catalysed by [Rh(Cy2PCH2PCy2)(η6-fluoroarene)][AlOF4] complexes, in weakly coordinating fluoroarene solvents is described. The subsequent discovery and optimization of a hydroacylation reaction of non-tethered aldehydes with acrylates, catalysed by a {Rh(DPEPhos)}+ catalyst system in 1,2-difluorobenzene is detailed.